O ENSINO CONFESSIONAL ADVENTISTA EM SÃO LUÍS/MA: Na Reminiscência da sua Trajetória Histórica as Pistas da sua Expansão - Ramos, Maély Ferreira Holanda (2010)
This present study is about of the Adventist Education Confessional in São Luís, Maranhão, during 1943 to 2010, having as a reference the Adventist College of São Luís because this is the first Educational Institution Network. The goal is to recover the research process and to analyze the historical reminiscence through discourses and practices and then to understand the conditions that favored and allowed the emergence and expansion of educational institution. Studies the Adventist Education Confessional entered the religious field of Maranhão in context of the plurality in the XIX and XX centuries. Considers that it is a place of symbolic manifestantion that put thoughts of competing interests dispute. Believes that it is a field of struggle where perceive conflicts arising from competition for power as a function of the legitimation of a symbolic order (SANTOS, 2006; BOURDIEU, 1990). It starts with the origin of Seventy-Day Adventist Church in United States and its expansionist movement that culminated with the introduction of the churc in Brazil, as well as its institutional extension: the school (SHUNEMANN, 2002; DOUGLASS, 2003). It is understand the Adventist College of São Luís to unveil the strategies used for its development and expansion, while proselytizing influence (SARAIVA, 2000; CERTEAU, 1988; FOUCAULT, 1979). Makes this study a qualitative approach based on oral history as an investigative method and cultural history while analytical axis from the reminiscences captures in open interviews and practices encountered during participant observation in two months in contact with the field research. It is postulated the analysis of memory as connections between past and present for the reconstruction of identity understanding the memory as oral narrative that can bring to mind the evidence political, economic, social, cultural and educational importance for the understanding of a story. It analyze and interpret the multiple relationships that are established in the religious of Maranhão in the Adventist Education Confessional to understand their connection with Seventy-Day Adventist Church and their educacional purpose, the goal and expansion strategies. It is assumed about adaptation to international market of São Luís to achive competitiveness in a progressive process opening for customer service other religions in a subtle distance of the established objectives at the beginning of his career.